Extraspinal articular tuberculosis: An 11-year retrospective study of demographic features and clinical outcomes in East London. Issue 3 (September 2020) - McGuire, Emma; Rajagopal, Swathi; Vaikunthanathan, Trishan; Krutikov, Maria; Burman, Matthew; Rahman, Ananna; White, Veronica; Tiberi, Simon; Rosmarin, Caryn; Kunst, Heinke
Highlights: Extra-spinal articular TB more commonly affected men and people of South Asian ethnicity. Significant avoidable healthcare-associated diagnostic delays were identified. A high index of clinical suspicion is needed for TB in individuals from high TB incidence regions. Abstract: Objectives: To describe demographic features, clinical outcomes and diagnostic delay amongst patients with extra-spinal articular tuberculosis (TB) in a low-incidence setting. Methods: Cases of TB treated at our institution between 2004 and 2014 were identified via the London TB register (LTBR). Demographic features of extra-spinal articular TB cases were compared to controls with TB at all other sites. For articular cases (excluding individuals <16 years or with spinal TB without peripheral joint involvement) clinical data were retrospectively collected. Results: 6, 146 TB patients were identified over the study period; 146 (2.4%) cases had extra-spinal articular infection. There was no difference in median age between extra-spinal articular TB cases and controls with TB at other sites (31 vs 32 years, p  = 0.57). Articular cases were more likely to be male (70.6% vs 59.5%, p  = 0.007), Bangladeshi (28.7% vs 18.0%) or Pakistani (24.0% vs 16.1%) and were less likely to be Black-African (9.5% vs 19.8%) ( p  < 0.001). 93 cases were included in the case series; 85 (88.5%) were migrants and 83 (89.2%) were South Asian. Knee and elbow joints were affected in 22 (23.7%) and 18 (19.4%) cases respectively. The median durations of pre-healthcare and healthcare associated delay were 16 and 6 weeks respectively. Where mycobacterial culture was performed, 57/75 (76%) were positive for Mycobacterium tuberculosis . 86 (92.5%) cases received standard quadruple therapy for a median of 6 months (IQR 6–9). Recurrence of TB infection occurred in 4 (4.3%) cases and there were no TB related deaths. Seven (7.6%) cases required surgical intervention. Conclusions: Extra-spinal articular TB more commonly affected men and people of South Asian ethnicity. Significant diagnostic delays were identified, including avoidable healthcare-associated delays.